Analysis of Factors Affecting System Success in E-Learning System of XYZ University Jakarta - Setiawan, Frans; Sfenrianto, Sfenrianto (Journal of Economics and Business UBS, 2023)
The e-learning system is currently a hot topic of conversation considering the Covid-19 pandemic situation which has hampered the teaching and learning process in various countries. XYZ University as one of the best technology universities in Indonesia has used the e-learning system long before the pandemic. Therefore, this research was conducted using quantitative methods to determine the factors that influence system success in the XYZ university e-learning system in hope that this research can be a benchmark as a effective solution. This study uses several literature studies including e-learning, and knowledge acquisition. Data analysis was carried out using the SEM method using the SmartPLS 3 application. There were 6 independent variables, namely information quality, system quality, service quality, system usage, user satisfaction, and knowledge acquisition. The dependent variable is system success. From the results of the questionnaire distribution, 385 respondents were obtained from XYZ university undergraduate students who are still actively studying out of a total of 418 respondents. A total of 224 respondents were male and 194 respondents were female. This study proposes 12 hypotheses that have 11 accepted hypotheses and 1 rejected final results. This research contain indicators per variable that used for the questionnaire also several data analysis process was served. The results show that the knowledge acquisition is positively influenced by system quality but not significant and the information quality have a significant positive effect on the knowledge acquisition. There are limitations in this study, where the selected respondents are limited by the researcher cause of some access to respondents. Further research can be conducted on students from various majors so that they can gain different perspectives for more concrete evidence. Further research can be carried out using other variables that support proving the factors that influence the success of the system using the DeLone and McLean models.